Pengelolaan Digital Public Relations Diskominfo Kabupaten Bogor (Studi Deskriptif Pada Pengelolaan Akun Instagram @kabupaten.bogor) - Rahmawati, Khafidhotur; Anugrah, Dadan; Tresnawaty, Betty (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
The research to find out deeply about the management of digital public relations on the @kabupaten.bogor Instagram account carried out by Diskominfo Bogor Regency referring to the concept of social media management, namely The Circular Model of Some by Regina Luttrell, through four stages including: share, optimize, manage and engage. The study used a qualitative approach with descriptive methods through interview and observation data collection techniques. The results of the study concluded that Diskominfo Bogor Regency in managing the Instagram account @kabupaten.bogor went through several stages. First, the Diskominfo share stage determines the social media you want to use so that it makes it easier to build relationships and trust. Second, at the optimize stage, Diskominfo pays attention to developments that occur on social media to study public desires and improve strategies. Third, Diskominfo at the manage stage conducts media monitoring which aims to see the spread of information flows. The last stage is engage, Diskominfo knows the existence of the audience with the aim of designing a better strategy so that information can be widely spread.